Study on drying of oil palm trunk with ethanol / Fauzi Othman … [et al.] - Othman, Fauzi; Yamani, Shaikh Abdul Karim; Sahat, Sa'diah; Shafie, Amran; Ahmad Zaki, Junaiza; Abd Latif, Nur Hannani; Mohamad, Aminuddin; Nik Hashim, Nik Hazlan; Kamarudin, Norashikin (2013)
Wood-based industry in Malaysia is dependent on the natural forest resources and forest plantations. The highly demand of this resource makes it more scarce and expensive. Currently the industries are searching for other resources to overcome the over dependence on local timber. The waste biomass from the oil palm industries can be turned into value-added products providing an alternative raw material for the wood industry, but OPTs (Oil Palm Trunk) are reported to be difficult to dry, not only because of its extremely high green moisture content, but also its drying defects. The objectives of this study are to characterize of drying defects in the OPT at different height (bottom to top) and layer of the trunk (bark to pith). To have different layer of trunk, the OPTs are sawn with sawing around pattern. Seventy two samples sized 25 mm thick x 100 mm wide x 200 mm long obtained from three palm trunks were soaked with 75% concentration of ethanol liquids and dried using the Terazawa's Quick During Test (QD1) Likert Method scale is used to rate the defect level of the sample between the of scale of I (free from a defect) to 5 (severe defect). Chi-squared independent test is conducted to determine the significant effect. The result showed a gradual increase in drying defect along the trunk height and depth. but no significant relationship between trunk portion and Layers. It is concluded that the OPT mixed with Ethanol can be dried with oven dry method a minimum time consumption produced minimum drying defect.